Pemberdayaan Masyarakat pada Kegiatan PKM Keagamaan di Masjid Baitul Muttaqin Desa Bulakan Kota Cilegon - Joni Prihatin; Juhandi Juhandi; Mastutiniyah Mastutiniyah; Marlina Marlina; Sri Lestari (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Community empowerment is an effort to increase the strength and abilities of the community so that they can be more independent and develop their potential. One of the community empowerment activities in Bulakan Village, Cilegon City, is the religious activity of routine Islamic recitation. Community service in the religious sector at KKM 42 Bina Bangsa University through regular recitations at the Baitul Muttaqin Mosque in the Bulakan Village area, Cibeber District, Cilegon City, Banten Province as part of increasing religious harmony, strengthening Islamic brotherhood, and creating tolerance. This community empowerment is carried out through routine Islamic religious activities, namely routine recitations and religious counseling. This routine activity is followed by some fathers and young people who already understand and implement it in their daily lives. So this community empowerment activity needs to be intensified and improved further as a baton in facing developments in time and technology so that there is continued peace and prosperity.